Behavioral changes after nicotine challenge are associated with α7 nicotinic acetylcholine receptor-stimulated glutamate release in the rat dorsal striatum. Issue 1 (December 2017) - Ryu, In; Kim, Jieun; Seo, Su; Yang, Ju; Oh, Jeong; Lee, Dong; Cho, Hyun-Wook; Yoon, Seong; Seo, Joung-Wook; Chang, Suchan; Kim, Hee; Shim, Insop; et al.
Abstract Neurochemical alterations associated with behavioral responses induced by re-exposure to nicotine have not been sufficiently characterized in the dorsal striatum. Herein, we report on changes in glutamate concentrations in the rat dorsal striatum associated with behavioral alterations after nicotine challenge. Nicotine challenge (0.4 mg/kg/day, subcutaneous) significantly increased extracellular glutamate concentrations up to the level observed with repeated nicotine administration. This increase occurred in parallel with an increase in behavioral changes in locomotor and rearing activities. In contrast, acute nicotine administration and nicotine withdrawal on days 1 and 6 did not alter glutamate levels or behavioral changes. Blockade of α7 nicotinic acetylcholine receptors (nAChRs) significantly decreased the nicotine challenge-induced increases in extracellular glutamate concentrations and locomotor and rearing activities. These findings suggest that behavioral changes in locomotor and rearing activities after re-exposure to nicotine are closely associated with hyperactivation of the glutamate response by stimulating α7 nAChRs in the rat dorsal striatum.